Investigation of high temperature rheological properties for attapulgite suspensions - Wenlong Zheng; Suzhou Wang; Lingguo Bai; Chiheng Yang (Scientific Reports)
Abstract Understanding the high temperature rheological characteristics of attapulgite suspensions is essential for addressing issues related to smooth rock support and wellbore stabilization during deep drilling in complex formations. Rheological measurements of attapulgite suspensions were carried out at temperatures of 40 °C, 70 °C, 100 °C, 160 °C, 190 °C, and 220 °C. The viscosity values obtained were analyzed to assess slurry forming behavior, and flow curves were fitted using Bingham, Herschel-Bulkley and Casson models. Additional experiments investigated different physicochemical conditions (clay addition 2–8 wt%; shear rate 5.11s− 1 to 1022s− 1; aging conditions; electrolyte (NaCl) concentration 5-35%) showed that there was a significant positive correlation between clay addition and suspension viscosity, but the temperature variations complicated the rheological responses. High shear rates allowed complete dispersion of attapulgite clay to form a suspension with stable viscosity. Aging positively influenced viscosity retention at high temperatures, despite some clay agglomeration. Sodium chloride and polymers significantly affected the high temperature rheological properties of the suspensions. The Bingham model effectively described the rheological properties of the suspensions above 190 °C. While attapulgite is recognized as a salt-resistant clay, our experimental results also demonstrate its significant temperature resistance when incorporated into drilling fluids.